Nanosystems for modulation of immune responses in periodontal therapy: a mini-review - Anirudh B. Acharya; Usha Hegde; Swetha Acharya (Frontiers in Dental Medicine)
Periodontitis is one of the most common oral diseases. It is generally treated by non-surgical and/or surgical therapy with adjunctive approaches for prevention and control. The current understanding of the pathogenesis of periodontitis has unraveled the importance of the inflammatory and immune reactions to combat periodontitis whose etiology is an overlap of microbial, genetic, and environmental factors in a susceptible host. Based on this premise, many therapeutic modalities have been investigated or attempted to resolve this inflammatory disease. Amongst these, nanomedicine has been shown to have therapeutic applications in periodontitis, especially focused on immunomodulation because periodontitis is characterized by over-reactive immune response. This mini-review explores the potential of nanosystems in treating periodontitis by providing an overview of the research efforts in this field of therapeutics. The unique physicochemical and targeting properties of nanosystems seem to be potentially effective platforms for treating periodontitis.